2004
DOI: 10.1007/bf02724095
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physical and mental activity on blood pressure

Abstract: Boys spent twice the time in outdoor playing than girls. They were spending more time on outdoor playing than on home study. Conversely girls spent more time in home study. A weak negative correlation was observed between outdoor playing and blood pressures. Less time spent in physical activities by the girls may have contributed to their higher BMI. They need behavior change communication for involvement in physical activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…A high number of hypertensive patients in this study had a low education level. This is in agreement with the findings of the report published by WHO which indicated that education is directly related to hypertension; illiterates being more susceptible (Thakor, Kumar, & Desai, 2014). Another study conducted by Hazarikas, Biswas, and Mahanta (2003) showed that prevalence of hypertension was high among patients with low education level compared to patients with high education level.…”
Section: Discussionsupporting
confidence: 90%
“…A high number of hypertensive patients in this study had a low education level. This is in agreement with the findings of the report published by WHO which indicated that education is directly related to hypertension; illiterates being more susceptible (Thakor, Kumar, & Desai, 2014). Another study conducted by Hazarikas, Biswas, and Mahanta (2003) showed that prevalence of hypertension was high among patients with low education level compared to patients with high education level.…”
Section: Discussionsupporting
confidence: 90%
“…The relationship between physical activity (PA) and BP in adults is well established, but findings in children have been inconsistent with few studies. Thakor et al, 2004, found that both SBP and DBP were significantly associated with outdoor playing taking the whole sample as one, but not in different sex or age group, except that the SBP was significantly correlated with outdoor playing in 10-13 years of age group in boys [8]. Hansen and Hyidebebrendt 1989 found an inverse correlation between blood pressure and physical fitness [9].…”
Section: Discussionmentioning
confidence: 99%
“…4 'Tracking' observed in the blood pressure values from childhood to adulthood shows a potential value of long-term approaches to hypertension control based on the prevention of high blood pressure in children. 5 The task force recommended that all children 3 years of age or older should have their blood pressure recorded during health maintenance visits and emergent visits. One of the most important developments in the past 5 years has been the publication of new blood pressure tables that are adjusted for height.…”
Section: Discussionmentioning
confidence: 99%